Application of Video Phonics Media Towards Pronunciation and Coqnitive Development of English Learning Children of Preschool Age Saint Nicholas Kindergarten Pantai Indah Kapuk Jakarta - Patrisia, Willsa; Widayat, Edy; Huda, Nuril (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to obtain information regarding the evaluation of the effectiveness of audio video to improve the phonics abilities of Kindergarten B children. This research is a quasi-experimental study, with a Pre-Test Post-Test Control-Group Design. The population in this study were all children in group B at Saint Nicholas Kindergarten Jakarta. Sampling using random sampling technique with a total sample of 50 children. Data collection was done by interview, observation, pre-test and post-test. Determining the effectiveness of the media used is tested by the Independent Sample T-Test. quasi experiment with nonequivalent control group design. The sampling technique uses systematic sampling. Data collection techniques used in the form of tests, interviews, observation and documentation. The validity of the instrument uses construct validity and product moment pearson correlation. Instrument reliability using Cronbach's alpha. Data analysis techniques used prerequisite tests and t tests which were processed using SPSS. 15 for windows.